Analisis Implementasi Program Kampus Mengajar Universitas Muhammadiyah Prof. Dr. Hamka - Novanita Whindi Arini; Ima Mulyawati (Jurnal Paedagogy, 2023)
This study aims to analyze the implementation of "Kampus Mengajar" to increase the academic community's participation and to find out the perceptions of students of Prof. Dr. Hamka Muhammadiyah University. This research method used an exploratory survey with a qualitative approach with respondents of Teaching Campus Students of Universitas Muhammadiyah Prof. Dr. Hamka Batch 4 and 5. The instrument used was a questionnaire distributed using Google Forms. The research data analysis technique was interactive analysis, which includes data reduction, data presentation, verification, and data validity checks. The validity of this research data used triangulation. The results of this study indicated that the MBKM program, especially the Teaching Campus of Muhammadiyah Prof. Dr. Hamka University, was well implemented from socialization to assessment. However, there were still differences of opinion regarding the conversion of SKS by students based on the perceptions of Muhammadiyah Prof. Dr. Hamka University students; several opinions and data were obtained regarding the policies felt by students.